2017
DOI: 10.1007/s00467-017-3684-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting in chronic kidney disease

Abstract: Loss of lean body mass is a relevant component of the cachexia, or protein energy wasting (PEW), syndrome. Reduced muscle mass seems to be the most solid criterion for the presence of cachexia/PEW in patients with chronic kidney disease (CKD), and those with greater muscle mass loss have a higher risk of death. Children with CKD have many risk factors for lean mass and muscle wasting, including poor appetite, inflammation, growth hormone resistance, and metabolic acidosis. Mortality risks in patients with CKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 80 publications
0
23
0
1
Order By: Relevance
“…Factors contributing to malnutrition in CKD include decreased nutrient intake secondary to accumulation of toxins, alteration of normal hunger and satiety regulatory hormones, inflammation, effect of peritoneal dialysis on sense of fullness, increased nutrient losses associated with dialysis, alterations in the growth hormone/insulin‐like growth factor axis, renal osteodystrophy, and in some cases increased nutrient needs and decreased intake . Some people advocate for terming malnutrition in CKD “protein‐energy wasting” because of multiple contributing factors outside of decreased nutrient intake alone and to better emphasize the complexity of malnutrition in CKD and loss of lean body mass …”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Factors contributing to malnutrition in CKD include decreased nutrient intake secondary to accumulation of toxins, alteration of normal hunger and satiety regulatory hormones, inflammation, effect of peritoneal dialysis on sense of fullness, increased nutrient losses associated with dialysis, alterations in the growth hormone/insulin‐like growth factor axis, renal osteodystrophy, and in some cases increased nutrient needs and decreased intake . Some people advocate for terming malnutrition in CKD “protein‐energy wasting” because of multiple contributing factors outside of decreased nutrient intake alone and to better emphasize the complexity of malnutrition in CKD and loss of lean body mass …”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…CKiD has accepted this advice and adapted adult criteria for the diagnosis of PEW so that they are applicable to children. They suggest a combination of nutritional, growth and biochemical parameters, including reporting of decreased appetite; BMI or mid upper arm circumference for height age (the age at which the height would be on the 50th centile) of < 5th centile or a decline of ≥ 10% over a year; height < 3rd centile for height age or a fall in percentile ≥ 10% over a year; serum albumin < 3.8 g/L; cholesterol < 100 mg/dL; and transferrin < 140 mg/ dL ( [6].…”
Section: How Do We Define Pew In Children With Ckd?mentioning
confidence: 99%
“…Recent studies showed that PD patients often present decreased levels of physical activity (PA) matching a sedentary lifestyle [2]. These circumstances significantly affect the health condition of those patients and are associated with significant morbimortality [3]. Moreover, the nutritional status and sedentary behavior directly affect muscle function, exercise performance, physical function, strength, and health-related quality of life [4][5][6].…”
Section: Introductionmentioning
confidence: 99%